Improving Students’ Speaking Skill through Play-Based Learning - Andreas, Aan; Regina, Regina; Riyanti, Dwi (Lectura : Jurnal Pendidikan, 2024)
Based on the syllabus on 4.8, 10-year students at Sekolah Menengah Kejuruan (SMK) Maniamas Ngabang must be able to present short and simple narrative texts related to folk legends. This research aims to improve students’ speaking skills through play-based learning. This research was a classroom action research. The procedures of this research covered planning, acting, observing and reflecting. The subjects of this research were 28 students of class X of SMK Maniamas Ngabang. The data were collected by observation checklist, field notes, speaking test, questionnaire, and interview sheet. The data obtained from the process of data collection were analyzed by reflecting on the facts or information gathered to assess the improvement of students' speaking. After collecting the data, the next step was analyzed the data. The data classified based on the research. In this study, the analysis used qualitative and quantitative analysis. This research showed play-based learning was able to improve students’ speaking skills. The students were more engaged in learning when the lesson presented involved games, and they also put more concerned about their assignments, attendance, and activities during the learning process. They stated that it became easier to understand the lesson because they can directly practice it the game application in the learning process. Last, the questionnaire result showed the students strongly agreed that play-based learning was a good method for learning to speak, with a mean value 4.54. In conclusion, the use of play-based learning can improve students’ speaking skill.